Pengaruh Independensi dan Kompetensi Auditor terhadap Kualitas Hasil Audit melalui Penggunaan Audit Technolgy : Studi Kasus pada Inspektorat Daerah Kabupaten Dompu - Kariani Kariani; M. Ikhwan Mansyuri; Rizky Ramadhan (Jurnal Mahasiswa Manajemen dan Akuntansi, 2026)
This study aims to comprehensively examine the direct effects of auditor independence and competence on audit quality, while also evaluating the mediating role of audit technology at the Dompu Regency Inspectorate. A quantitative approach was used with primary data collected via a questionnaire. Using a census method and specific inclusion criteria, this study obtained a valid sample of 45 auditors with at least one year of audit experience at the Dompu Regency Inspectorate, West Nusa Tenggara. The framework involved four variables: auditor independence, auditor competence, audit technology, and audit quality. Data analysis was conducted using Partial Least Squares-Structural Equation Modeling (PLS-SEM) via SmartPLS 4.0 software. The PLS-SEM analysis showed that auditor competence and audit technology have a significant positive direct effect on audit quality. Interestingly, auditor independence does not directly affect audit quality. Auditor competence was also found to significantly increase the use of audit technology, whereas auditor independence did not. Furthermore, audit technology was not found to significantly mediate the effects of either auditor competence or auditor independence on audit quality. This indicates that, in the context of this study, audit technology plays a more dominant role as a direct predictor of audit quality than as a mediating mechanism for auditor competence or independence. Theoretically, this study enriches Agency Theory by confirming that the independence of internal auditors embedded within the very organizational structure they oversee tends to be less effective without the support of other mechanisms, while competence remains the primary determinant of audit quality both directly and through the use of audit technology in line with the propositions of the Technology Acceptance Model (TAM). Practically, these findings encourage local governments to prioritize programs to enhance auditor competence through training and certification, as well as investment in audit technology, rather than merely emphasizing formal independence, in order to strengthen local financial accountability. Further research is recommended to expand the sample scope to include several other regional inspectorates and to explore other factors outside the model, such as management support and information technology infrastructure.